2016
DOI: 10.1037/fam0000188
|View full text |Cite
|
Sign up to set email alerts
|

Single mothers by choice: Mother–child relationships and children’s psychological adjustment.

Abstract: Fifty-one solo mother families were compared with 52 two-parent families all with a 4–9-year-old child conceived by donor insemination. Standardized interview, observational and questionnaire measures of maternal wellbeing, mother–child relationships and child adjustment were administered to mothers, children and teachers. There were no differences in parenting quality between family types apart from lower mother–child conflict in solo mother families. Neither were there differences in child adjustment. Percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 52 publications
8
76
2
1
Order By: Relevance
“…Similar to findings of research with donor‐conceived children in two‐mother families (Raes and others, ; Van Parys and others, ; Vanfraussen and others, ), it seems that the social world of the children in this study may be characterised by assumptions about what families are and/or ought to be like. Although the children who participated were found to be generally well‐adjusted (Golombok and others, ), amendments to the school syllabus that emphasise family diversity, and the implementation of teaching resources about single‐parent families akin to those developed about same‐sex parents (Guasp, ), may now be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to findings of research with donor‐conceived children in two‐mother families (Raes and others, ; Van Parys and others, ; Vanfraussen and others, ), it seems that the social world of the children in this study may be characterised by assumptions about what families are and/or ought to be like. Although the children who participated were found to be generally well‐adjusted (Golombok and others, ), amendments to the school syllabus that emphasise family diversity, and the implementation of teaching resources about single‐parent families akin to those developed about same‐sex parents (Guasp, ), may now be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…One answer is found in Walker et al's (:173) suggestion that anchoring arguments about ARTs in ‘archaic’ structures of meaning enables evasion of the ‘opprobrium of being unjust and discriminatory’. With regard to single mothers by sperm donation, it is clear that media representations bear little relation to the psychological literature that has shown that this user group – and their children – are psychologically well‐adjusted, and their families are characterised by positive mother–child relationships (Golombok, Zadeh, Imrie, Smith, & Freeman, ). It is also noteworthy that such representations proliferate despite regulatory changes that now explicitly permit the use of donor sperm by single women (Human Fertilisation and Embryology Act, ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a section of the interview that focused on the mother–child relationship and the psychological adjustment and experiences of the child are reported elsewhere (Golombok et al., 2016). All mothers gave written informed consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%